Quality of life, life satisfaction and happiness in shift- and non-shiftworkers - Kaliterna,Lipovcan LJ (2004)
OBJECTIVE: To investigate the quality of life, life satisfaction, happiness and demands of work in workers with different work schedules. METHODS: The survey was carried out on professional workers in social care. Some were shiftworkers whose schedule included night shifts (N=311), some were shiftworkers without night shifts (N=207) and some were non-shiftworkers (N=1,210). Surveys were mailed and the response rate was 86%. For the purpose of this study several variables were selected from the Survey: The Quality of Life Profile, which measures importance, satisfaction, control and opportunities in nine domains of life plus measures of happiness, life satisfaction and demands of work. RESULTS: While both groups of shiftworkers, compared to non-shiftworkers, reported needing more physical effort to complete their work, and reported 'being' more physically tired, no differences were found in reports of overall happiness, life satisfaction or total quality of life. However, night-shiftworkers reported greater percentage of time unhappy than the other two groups of workers. In analyses of the quality of life, night-shiftworkers were less satisfied with domains of spiritual 'being' and physical and community 'belonging' than day-shiftworkers and non-shiftworkers. They also reported having fewer opportunities to improve their physical 'being', leisure, and personal growth than the other two groups. CONCLUSIONS: Quality of life in specific domains in night-shiftworkers was rated worse than in other groups of workers. Domain-based quality of life assessment gives more information regarding the particular needs of workers than overall or global measures of well-being.